2015
DOI: 10.1186/s40170-015-0130-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy and cancer

Abstract: Mitophagy is a selective form of macro-autophagy in which mitochondria are selectively targeted for degradation in autophagolysosomes. Mitophagy can have the beneficial effect of eliminating old and/or damaged mitochondria, thus maintaining the integrity of the mitochondrial pool. However, mitophagy is not only limited to the turnover of dysfunctional mitochondria but also promotes reduction of overall mitochondrial mass in response to certain stresses, such as hypoxia and nutrient starvation. This prevents ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
189
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(190 citation statements)
references
References 134 publications
(185 reference statements)
1
189
0
Order By: Relevance
“…In addition to the core factors in the autophagy, previous studies have revealed that specific regulators such as BNIP3, NIX, Parkin, Pink1 and FUNDC1 are required for promoting mitophagy (31,(34)(35)(36). Recently, emerging evidence has revealed that deregulation in key regulators of mitophagy is found in several cancers and suggested a possible implication in tumorigenesis (34). For instance, Parkin located at human chromosome 6q25-q26 is frequently deleted in bladder, lung, breast and ovarian cancers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the core factors in the autophagy, previous studies have revealed that specific regulators such as BNIP3, NIX, Parkin, Pink1 and FUNDC1 are required for promoting mitophagy (31,(34)(35)(36). Recently, emerging evidence has revealed that deregulation in key regulators of mitophagy is found in several cancers and suggested a possible implication in tumorigenesis (34). For instance, Parkin located at human chromosome 6q25-q26 is frequently deleted in bladder, lung, breast and ovarian cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial autophagy, designated as mitophagy, is a selective form of autophagy in which mitochondria are degraded in autolysosomes (31,32). Mitophagy represents a critical adaptive mechanism to maintain oxygen homeostasis and to eliminate old and/or damaged mitochondrion in response to certain stresses including hypoxia (33,34). In addition to the core factors in the autophagy, previous studies have revealed that specific regulators such as BNIP3, NIX, Parkin, Pink1 and FUNDC1 are required for promoting mitophagy (31,(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although BRCA2 functions have so far taken place in the nucleus, a recent study raises the intriguing possibility that BRCA2, along with BRCA1 and multiple proteins of the FA pathway (FANCA, FANCF, FANCL, FANCD2), facilitates mitophagy, a cytoplasmic process that targets damaged mitochondria to selective autophagy (Sumpter et al 2016). Mitophagy is critical to maintain low level of mitochondrial reactive oxygen species (mtROS), and recent evidence suggests that the accumulation of mtROS impacts transformation and tumors progression (Chourasia et al 2015). Therefore, understanding BRCA2 functions in the cytoplasm may shed new light on its role as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative mechanism ( Figure 2B), most well studied during hypoxia-induced mitophagy involves two molecular regulators, BNIP3 and NIX (Zhang and Ney, 2009), which are targets of the hypoxia inducible factors (HIFS) (Guo et al, 2001) as well as other transcription factors including NFkB and P53 (Fei et al, 2004;Feng et al, 2011;Shaw et al, 2008) Inhibition or disruption of BNIP3/NIX function can lead to non-apoptotic cell death suggesting their roles in quality control are critical (Chourasia et al, 2015).…”
Section: Molecular Physiology Of Mitochondrial Quality Controlmentioning
confidence: 99%